2011
DOI: 10.1530/jme-11-0023
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of human thyroid cancer in relation to its mutational status

Abstract: This review describes the gene expression profile changes associated with the presence of different mutations that contribute to thyroid cell carcinogenesis. The results are discussed in the context of thyroid cancer biology and of the implications for disease prognosis, while the diagnostic aspect has been omitted. For papillary thyroid cancer (PTC), the most characteristic gene expression profile is associated with the presence of BRAF mutation. BRAF-associated PTC differ profoundly from RET/PTC or RAS-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 116 publications
1
16
0
Order By: Relevance
“…Various genetic arrays have revealed a plethora of abnormalities in these lesions including chromosomal deletions, amplifications, and fusions; activating/inactivating point mutations in known oncogenes and tumor suppressor genes; and alterations in epigenetic regulators. Adaptations in molecular factors thought to contribute to ATC progression are numerous (1,34,35). Gene array analysis of ATC patient samples illuminated significant alterations in fatty acid metabolism in these tumors (Figure 1A and Supplemental Table 1), presenting an innovative therapeutic opportunity for this aggressive malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Various genetic arrays have revealed a plethora of abnormalities in these lesions including chromosomal deletions, amplifications, and fusions; activating/inactivating point mutations in known oncogenes and tumor suppressor genes; and alterations in epigenetic regulators. Adaptations in molecular factors thought to contribute to ATC progression are numerous (1,34,35). Gene array analysis of ATC patient samples illuminated significant alterations in fatty acid metabolism in these tumors (Figure 1A and Supplemental Table 1), presenting an innovative therapeutic opportunity for this aggressive malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although derived from follicular epithelium of the thyroid gland, ATC cells do not retain any biological feature of the original cell type as a result of multiple mutational events leading to dedifferentiation. A number of gene expression studies in ATC yielded evidence of the upregulation of genes involved in cell cycle progression and chromosome segregation, among which were the Aurora kinases (Salvatore et al 2007, Wiseman et al 2007, Rusinek et al 2011. In particular, Aurora-A has been identified among the most frequently and strongly overexpressed proteins in ATC, and high expression of Aurora-B has been also reported (Sorrentino et al 2005, Ulisse et al 2006, Wiseman et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Adeniran et al [86] reported RET/PTC rearrangements presented at younger age and had predominantly typical papillary histology, frequent psammoma bodies and a high rate of lymph node metastases, but these findings might be related to the higher frequency of lymph node metastases observed in young patients, and it is not an important prognostic factor for this age group [32]. RET/PTC rearrangements are quite frequent in radiation-induced PTC as well [87].…”
Section: The Challenge Of Prognosis Based On a Molecular Profilementioning
confidence: 99%